The Bologna process between structural convergence and institutional diversity - Dunkel, Torsten [Verfasser] (My University, 2009)
"The merging of the Bologna and the Copenhagen processes into a single European education area appears appropriate, especially as general, vocational, adult and academic education are to be integrated in a future European Qualification Framework (EQF). This is the backdrop to the following description of the Bologna process, which was originally intended as a European unifying blueprint for the reorganisation of study structures and university degrees but which mutated during its implementation into a surprising array of internationally diverse local reform efforts and outcomes." (Autorenreferat, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; G 2.5.3 Anschlussfähigkeit von Bildungsgängen; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.2 Europa; EU-Bildungspolitik; Bildungsreform; Bologna-Prozess; Studienabschluss; Bachelor; Master; Europäischer Qualifikationsrahmen; Europa